FZD8, a target of p53, promotes bone metastasis in prostate cancer by activating canonical Wnt/β-catenin signaling. (28th August 2017) - Li, Qiji; Ye, Liping; Zhang, Xin; Wang, Min; Lin, Chuyong; Huang, Shuai; Guo, Wei; Lai, Yingrong; Du, Hong; Li, Jun; Song, Libing; Peng, Xinsheng
Abstract: Prostate cancer (PCa) is the second most frequently diagnosed cancer among men and exhibits a high propensity to metastasize to bone. Currently, bone metastasis remains incurable, and therapies are limited. A better understanding of the molecular mechanisms involved in PCa bone metastasis is needed to develop more effective therapeutics for this disease. Herein, we reported that among the FZD family, FZD8 was robustly upregulated in bone-metastastic PCa cell lines and tissues. High levels of FZD8 expression were significantly positively associated with clinical tumor progression and bone metastasis. Furthermore, we found that overexpressing FZD8 promoted, whereas silencing FZD8 suppressed, PCa cell migration, invasion and stem cell-like phenotypes in vitro, through the activation of canonical Wnt/β-catenin signaling. Importantly, downregulation of FZD8 greatly suppressed the incidence of PCa bone metastasis in vivo . Moreover, wild-type p53 transcriptionally repressed FZD8 by directly interacting with the FZD8 promoter. Taken together, these findings uncover a novel mechanism for PCa bone metastasis, and indicate that FZD8 might represent a potential therapeutic target for PCa bone metastasis. Highlights: Overexpression of FZD8 correlates with PCa tumor progression and bone metastasis. FZD8 enhances PCa cell migration, invasion, and stem cell-like phenotypes in vitro and bone metastatic capacity in vivo. Wnt/β-catenin signaling mediates FZD8-induced PCa cell metastasis and stem cell-like phenotypes. Wt-p53 transcriptionally represses FZD8 by directly interacting with the FZD8 promoter.